THE ROLE OF THE SUB-DISTRICT HEAD'S LEADERSHIP IN PUBLIC SERVICES AT THE LEIHITU SUB-DISTRICT OFFICE, CENTRAL MALUKU REGENCY - Armisa, Suci; Sahetapy, Petronella; Pattimukay, Hengky V. R. (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2024)
This research was conducted at the Leihitu Sub-District Office, Central Maluku Regency, with the aim of understanding how the leadership role of the Sub-District Head affects public services at the office. To achieve this objective, data analysis was carried out quantitatively using the Spearman Rank correlation formula as the measurement tool. The results of the analysis using Spearman Rho or Spearman Rank correlation showed a positive correlation between the Sub-District Head's leadership role and the quality of public services, with a correlation coefficient of 0.601. This figure indicates that the relationship between these two variables is strong, as it falls within the coefficient value range of 0.60-0.799. The strength of this relationship suggests that the better the leadership role performed by the Sub-District Head, the higher the quality of public services at the Leihitu Sub-District Office. Furthermore, the hypothesis test on the correlation coefficient revealed that the ρ-calculated value of 0.601 is greater than the ρ-table value of 0.388. This result indicates that the null hypothesis (Ho), which states that there is no relationship between the Sub-District Head's leadership role and public services, is rejected, while the alternative hypothesis (Ha), which asserts that there is a relationship between the two variables, is accepted. Thus, this study concludes that there is a significant and meaningful relationship between the Sub-District Head's leadership role and public services at the Leihitu Sub-District Office, Central Maluku Regency. This highlights the importance of effective leadership in improving the quality of public services at the sub-district government level.